Examining Faculty Perceptions of Distance Course Quality Review Feedback - Kristy Plander; Renee Hathaway; Deb Maeder (Online Learning)
The purpose of this explanatory sequential mixed methods study was to examine faculty perceptions of distance course quality review feedback at a small healthcare-focused college in the United States. The Examining the Evaluator Feedback Survey tool was adapted and used to determine faculty perceptions (N=16) of five key aspects of reviewer feedback (usefulness, accuracy, credibility, access to resources, and responsiveness) and the importance of feedback characteristics. Follow-up interviews (N=3) were conducted for in-depth exploration of survey results. Results indicated that faculty perceived feedback to be useful and accurate and reviewers to be credible. However, faculty would like to have more involvement both to explain their teaching context and to clarify and prioritize results. While receiving feedback was initially unpleasant and the amount of feedback may be overwhelming, faculty responded by using it to make course improvements. The study adds to limited faculty perception research amongst extensive research on quality tools and institutional review processes.